Dynamic weakening of serpentinite gouges and bare surfaces at seismic slip rates. Issue 11 (17th November 2014) - Proctor, B. P.; Mitchell, T. M.; Hirth, G.; Goldsby, D.; Zorzi, F.; Platt, J. D.; Di Toro, G.
Abstract To investigate differences in the frictional behavior between initially bare rock surfaces of serpentinite and powdered serpentinite ("gouge") at subseismic to seismic slip rates, we conducted single‐velocity step and multiple‐velocity step friction experiments on an antigorite‐rich and lizardite‐rich serpentinite at slip rates (V) from 0.003 m/s to 6.5 m/s, sliding displacements up to 1.6 m, and normal stresses (σn) up to 22 MPa for gouge and 97 MPa for bare surfaces. Nominal steady state friction values (μnss) in gouge at V = 1 m/s are larger than in bare surfaces for all σn tested and demonstrate a strong σn dependence; μnss decreased from 0.51 at 4.0 MPa to 0.39 at 22.4 MPa. Conversely, μnss values for bare surfaces remained ~0.1 with increasing σn and V. Additionally, the velocity at the onset of frictional weakening and the amount of slip prior to weakening were orders of magnitude larger in gouge than in bare surfaces. Extrapolation of the normal stress dependence for μnss suggests that the behavior of antigorite gouge approaches that of bare surfaces at σn ≥ 60 MPa. X‐ray diffraction revealed dehydration reaction products in samples that frictionally weakened. Microstructural analysis revealed highly localized slip zones with melt‐like textures in some cases gouge experiments and in all bare surfaces experiments for V ≥ 1 m/s. One‐dimensional thermal modeling indicates that flash heating causes frictional weakening in both bare surfaces and gouge. Friction values for gouge decrease at higher velocities and after longer displacements than bare surfaces because strain is more distributed.